STRATEGI ORANG TUA DALAM MENGATASI PEMBELAJARAN DARING KELAS 6 DI KELURAHAN TAWANGSARI KECAMATAN WONOSOBO - Budiarti, Annisa; Hidayat, Muhtar Sofwan (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2020)
The aims of study are 1) knowing the problems of parents in dealing with 6th grade online learning in Tawangsari Wonosobo Village, 2) knowing the application of parental strategies can make the right solution for preparing for school exams during online learning and knowing strategic solutions between parents with one another in Tawangsari Wonosobo village for grade 6 students. The type of research in this study is field research with qualitative methods, with in-depth analysis research techniques. Data collection that use in this study are, interviews, observation, and documentation. Data analysis technique that using in this study was data reduction (summarizing data), data presentation (data display), and conclusions. The result of this study is showed that the strategy of parents in solving these online learning problems, many parents choose to register or include their children in tutoring studios. In addition to being accompanied by professional educators to prepare for school exams and others, in the tutoring studio, children will pay more attention to materi that given.